Effective building materials using technogenic waste and mineral raw materials - Berdnikova Liliya; Gorbunov Fedor; Lapin Andrey (MATEC Web of Conferences, 2021)
The results of research on the development of compositions of construction materials for structural purposes based on technogenic waste and mineral raw materials are presented. The possibility of obtaining materials with a wide range of operational properties by the methods of slip casting (compressive strength of the samples based on chamotte and sand is 53.0–95.9 and 50.0-69.5 MPa, bending strength is 8.1–16.5 and 8.5–15.3 MPa, abrasion is 0.2–0.36 and 0.15–0.39 g/cm2, respectively) and semi-dry pressing (compressive strength of the samples based on chamotte and sand are 19.1–43.5 and 18.3–32.6 MParespectively) isdemonstrated.